Eﬀect of tourism in the economy of the Tacna region - Pinto Ranilla, Paulino Celso (2020)
The research worked deals with the activity of tourism located in the Tacna Region, an activity that in the last ten years has become one of the most incident activities in the economic life of the Region. The ﬂow of Chilean tourists arriving in the city of Tacna on average of 3000 daily visitors has generated positive impacts on the activities of commerce, gastronomy, hotels and restaurants, manufacturing and construction. At work, the evolution of the ﬂow of Chilean tourists that the city of Tacna has been receiving in the period 2003 to 2017 is analyzed. It is a work of the relational type and of documentary analysis, having collected the GDPand ﬂow data tourism of the oﬃcial publications of Peru, as well as theoretical references referring to the impact assessment have been used. The relationship of economic activities to tourism with other activities has been studied, ﬁnding considerably high and sustained relationships. It is demonstrated that indeed the arrival of tourists has an impact on the growth of the economy of the Tacna region.